THE VOCATION, MISSION AND SPIRITUALITY OF THE CHRISTIAN FAMILY IN THE LIGHT OF THE CHURCH FAMILY OF GOD ECCLESIOLOGY - Appiah-Kubi, Francis (Asian Horizons, 2015)
The human family, basic cell of the society, composed of father, mother and children, is universally founded on marriage whose laws and customs vary. Through sacramental bond such family becomes the Domestic Church, the miniature church in the house. Though, this paper focuses on the vocation and mission of the nuclear family, the complex network of relationship and solidarity that exists among families across generations cannot be excluded. The paper underlines and draws attention to human deficiencies and aberrations within the family in order to appreciate the Christian understanding of marriage and family institutions according to the mind of the Creator. It treats the nature and the vocation of Christian family; its foundation on the Trinity and spells out some aspects of its mission and spirituality. Briefly, it is a theological reflection on the revealed knowledge about Marriage and family life in the light of the theology of the Church Family of God.